Archaeometric analysis of building mortars used in the historic centre of Siena (Italy) between the 13th and 16th centuries. (February 2021) - Scala, Andrea; Gabbrielli, Fabio; Giamello, Marco; Mugnaini, Sonia
Highlights: Mortars from 13 th –16 th centuries masonries of Sienese grand buildings are analysed. Medieval mortars were made with aerial lime binders. Natural hydraulic binders were used since the second half of the 15 th century. A change of the lime stones supply sites over the centuries is established. Sandy aggregates were derived from local Pliocene sands and sandstones. Abstract: This work is part of a broader research concerning the ancient mortars used to build the historic centre of Siena (Italy). It is focused on the archaeometric analysis of twenty-three mortars samples selected from well-dated 13 th –16 th centuries masonries belonging to five monumental buildings (Cathedral, City Hall, city walls, Medicean Fortress, and Santa Maria della Scala hospital). The main compositional and technological features of the mortars were determined by means of thin section analysis with polarized light microscopy and chemical analyses of lumps with ICP-OES and ICP-MS. After a thorough documentary research, reference samples of selected rocks (Cavernous Limestone, Montagnola Senese Marbles, Alberese Limestone) were gathered from the Montagnola Senese area and from the southern sector of Chianti hills (west and north east of Siena, respectively) and analysed with the same chemical techniques, targeting the identification of possible types of raw materials used for the production of the lime binders. The study led to a first compositional and technological database of the ancient Sienese mortars and allowed verifying the change over time of the supply of raw materials for binder production. Mortars dating back before the middle of the 15 th century were obtained with aerial lime binders, whereas in later years natural hydraulic lime binders prepared from impure limestones were preferentially used. As regards the provenance of stones for lime, the obtained data suggest a transition over time from the exploitation of rocks from Montagnola Senese (preferred during the Middle Ages for lime production) to a prevalent use of Alberese Limestone from southern Chianti hills after the middle of the 15 th century. Throughout the entire period under examination, sandy aggregates were obtained from Pliocene sea deposits cropping out around the city.